Evaluation of drug information services in a tertiary care hospital in kanchipuram district and community pharmacies in neighbouring areas - G, Rajanandh M; V, Ruby; C, Ramasamy (Indian Journal of Pharmacy Practice)
Drug information service refers to activities carried out by pharmacists in providing any drug related information to healthcare professionals to provide better patient care. The study was aimed to evaluate the drug information services provided by a drug information centre in a teaching hospital in Kanchipuram district and community pharmacies in neighbouring areas. A total of 158 queries were received which were retrospectively evaluated for a period of six months, from August 2010 to January 2011. Majority of the enquirers were the interns (44.3%) and physicians (25.9%), from the general medicine department (56.3%). Most of the questions were asked by direct access (86.7%). Answers to queries were most often needed immediately (48.1%) and in most cases was answered verbally (56.3%). Most frequently asked questions were about adverse drug reactions (30.3%) followed by dosage and indication (27.8%) and the purpose of the queries were for better patient care (44.9%) and to update knowledge (40.03%). The quality of drug information services provided was assessed both from the receivers' as well as from the providers' perspective using feedback questionnaires and guidelines from the DSE/WHO seminar respectively. Assessment of the feedback questionnaire indicated that majority of the enquirers (98.2%) found the quality of the service provided by the centre to be satisfactory. Evaluation of queries answered by the centre from the providers' perspective revealed that they were within the acceptable limits of quality. In conclusion, the services provided by the centre cater to the need of healthcare professionals towards better patient care.
Keywords: Drug information service; Drug information Centre; Pharmacist; Healthcare professionals